2023
DOI: 10.1039/d3cc00191a
|View full text |Cite
|
Sign up to set email alerts
|

Current developments of eco-friendly organic field-effect transistors: from molecular engineering of organic semiconductors to greener device processing

Abstract: Replacing environmentally damaging toxic halogenated/aromatic hydrocarbon organic solvents commonly used in solution-processed organic field-effect transistors with more sustainable green solvents has in recent years become a subject of various studies....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Additionally, molecular design of organic semiconductors to enable thin film processing in ecologically friendly organic solvents (and water) has seen a significant amount of interest for the fabrication of OTFTs and organic photovoltaics. 165 Relevant reviews on sustainable materials synthesis has been reported by Phan and Luscombe, 166 and Marrocchi et al , 167 while reviews on green materials and processing of organic semiconductors to achieve less environmentally-harmful device fabrication processes have been published by Mooney et al , 168 Lee et al , 169 and Torricelli et al 170 A systematic study of green solvents to process a range of p- and n-type semiconductors including TIPS-pentacene, P3HT and perylene diimides was undertaken by Ho et al to study the effect of processing solvent on OTFT performance to develop general guidance for more sustainable device fabrication. 88 TIPS-pentacene processed from isobutyl acetate on a propylene glycol monomethyl ether acetate (PGMEA)-processed cellulose cinnamate gate dielectric achieved mobilities up to 2.6 cm 2 V −1 s −1 and an on/off current ratio of 10 4 .…”
Section: Future Developments In Otft Processing and Applicationsmentioning
confidence: 99%
“…Additionally, molecular design of organic semiconductors to enable thin film processing in ecologically friendly organic solvents (and water) has seen a significant amount of interest for the fabrication of OTFTs and organic photovoltaics. 165 Relevant reviews on sustainable materials synthesis has been reported by Phan and Luscombe, 166 and Marrocchi et al , 167 while reviews on green materials and processing of organic semiconductors to achieve less environmentally-harmful device fabrication processes have been published by Mooney et al , 168 Lee et al , 169 and Torricelli et al 170 A systematic study of green solvents to process a range of p- and n-type semiconductors including TIPS-pentacene, P3HT and perylene diimides was undertaken by Ho et al to study the effect of processing solvent on OTFT performance to develop general guidance for more sustainable device fabrication. 88 TIPS-pentacene processed from isobutyl acetate on a propylene glycol monomethyl ether acetate (PGMEA)-processed cellulose cinnamate gate dielectric achieved mobilities up to 2.6 cm 2 V −1 s −1 and an on/off current ratio of 10 4 .…”
Section: Future Developments In Otft Processing and Applicationsmentioning
confidence: 99%
“…This intricate pursuit encompasses the modification of pre-existing molecules or the creation of entirely unprecedented ones. Given the fact that structure plays a pivotal role in determining the material properties, the strategy of molecular engineering emerges as the fundamental starting point for the bottom-up design of OSCs, serving as the very essence of regulating supramolecular-assembly. , Drawing on these empirical observations, we summarize our endeavors on the regulation of supramolecular assembly, by bringing up a three-component OSC model with (i) a conjugated π core, (ii) an alkyl linker, and (iii) a polar head (Figure a). In particular, the conjugated π core was chosen to facilitate charge-carrier transport in OSCs through efficient [π···π] stacking. The head groups are grafted for further functionalization by involving noncovalent interactions.…”
Section: Molecular Engineering Of Oscs To Install Supramolecular Asse...mentioning
confidence: 99%